'Supreme Emergencies', ontological holism, and rights to communal membership. Issue 4 (4th July 2017) - Reiner, J. Toby
Abstract : This paper highlights the importance to just war theory of ontological questions about the constitution of personal identity. It does so through a critical reinterpretation of Michael Walzer's invocation of a supreme emergency exemption to the principles of jus in bello . Walzer's argument has been widely criticised for attaching more importance to communities than to individuals. I argue that his position normatively prioritises individuals, but is grounded in a holistic ontology. He valorises political community only because of its importance to the individuals who comprise it. On this view, each community forms a moral world and shapes individual identity. This gives individuals a highest order interest in being part of an autonomous community and makes threats to communal existence a form of moral disaster. The paper concludes that the debate about supreme emergency should engage with ontological questions, and that such engagement would mean problematising the study of what liberalism demands in international ethics.